EDITORIAL (American Journal of Islam and Society, 1994)
The first paper in our present issue is by Abdullah H. M. a1 Khalifahand examines how religiosity in an Islamic context serves as a protectivemechanism against criminal temptation. This is done, in short, by placingthe concept of law in the realm of religion, which means that criminalactivity is seen as a violation of God’s law before it is seen as a violationof a person’s rights. Such a perspective also reinforces the awareness ofthe certainty and severity of punishment in the afterlife. The author arguesthat Islam provides a unique social control perspective, one that hasaccounted for the main parameters that underlie the mechanisms of socialcontrol: religion, morality, and law. He first reviews the theories andliterature concerning the religion-crime relationship and then proceeds todiscuss the meaning of religiosity in Islam and how it has been transformedinto a valuable force for crime control. He concludes his analysiswith a discussion of the elements of Islamic ideology that constrain criminalbehavior.Muhammad al-Ghazali calls for a study of Sh& Wali Allah’s thoughtin greater depth, for the exceptionally futuristic thrust of his ideas areextremely relevant and promising for contemporary and future Islamicthought. He chooses to study Shah Wali Allah’s synthesis of reason,revelation, and empiricism, which he claims has been unrecognized bymany earlier and contemporary scholars. Al-Ghazali shows how ShahWali All& builds evidence from an inductive survey of social phenomenato substantiate the contentions of revelation while remainingwithin the doctrinal framework of revealed guidance and thus constructsa paradigm of universal social culture. Also covered is Shah Wali Allah’sanalysis of what separates human beings from animals and how theformer, due to their inherent and God-given instincts, develop civilization.Muhammad Hashim Kamali discusses the possibility of price control(tus‘fr) in Islam law. He shows that Islam did not promulgate any lawthat limits profits and fixes prices. He also examines several provisionsconcerning price control and highlights some of the conflicting interestsof freedom vs. authority that are reflected in relevant Shari‘ah provisions.The underlying issue of his research is the extent to which price controlsmay or may not impinge on the basic freedom of trade and of the individualto sell items at the regular market price as opposed to one fixed ...